Diabetic Foot Exercise to Reduce High Blood Sugar Levels in Diabetes Mellitus Patient: A Case Study - Musarrofa, Faise Lailatul; Rondhianto; A’la, Muhammad Zulfatul; Sujarwanto (Al-Hijrah Indonesia, 2024)
Diabetes mellitus is a metabolic disorder in the pancreas organ so that sugar levels increase due to a decrease in the amount of insulin in the pancreas. Therapeutic management pharmacology, namely administering insulin and administering oral hypoglycemic drugs, while non-pharmacological includes health education, diet, and exercise or physical training such as diabetes foot exercises. This research uses a case study method using pre and post methods carried out before and after the intervention. The data collection location was in the Lavender room at dr. Soebandi Hospital starts on 30 October 2023. Based on these results, it shows a change in blood sugar levels before and after administering diabetic foot exercise therapy is carried out for three consecutive days once a day, carried out in the morning 1-2 hours after breakfast. Diabetic foot exercises that are done regularly are expected to prevent complications often occurs in patients such as infected wounds on the feet. The results of the nursing evaluation are related to the diagnosis of instability in blood glucose levels which indicates changes in the patient's blood sugar levels where the patient's blood sugar values decreased after the intervention.